5-Hydrazinylethylidenepyrimidines effective against multidrug-resistant Acinetobacter baumannii: Synthesis and in vitro biological evaluation of antibacterial, radical scavenging and cytotoxic activities - Figueiredo, Joana (2020)
Acinetobacter baumannii has emerged as an important nosocomial pathogen in recent years, with infectious outbreaks caused by multidrug-resistant strains increasing worldwide. Thus, new antibacterial treatments for multidrug-resistant A. baumannii strains are needed. In this work, a series of 5-hydrazinylethylidenepyrimidines were synthesized and in vitro evaluated against two multidrug-resistant A. baumannii strains (AcB 13/10 and AcB 73/10). Minimum inhibitory concentration results demonstrated that generally the compounds in study presented values in a low micromolar range. In the determination of in vitro bacterial growth at 24 h, it was observed that the pyrimidines 3a and 3c, with an unsubstituted hydrazinylphenyl, have bacteriostatic activity in both multidrug-resistant A. baumannii strains, with a concentration-dependent action. In general, an additive effect occurred in the combination of these compounds with gentamicin, rifampicin and polymyxin B, for both strains. Furthermore, all 5-hydrazinylethylidenepyrimidines under study presented a good 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity, generally low xanthine oxidase inhibition and low cytotoxicity in normal human dermal fibroblasts as well as potential favorable drug-likeness properties. Thus, these molecules can be considered attractive for the future development of antibacterial agents against multidrug-resistant A. baumannii.